2023
DOI: 10.33423/jhetp.v23i1.5783
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Medicine and Health Training for Thai General Practitioners (GP): A SEM Analysis

Abstract: The study aimed to determine which factors affected a Thai general practitioner's (GP) intent to take integrative medicine and health (IMH) training. From the literature review, it was noted that IMH has other similar programs globally with names such as complementary and alternative medicine (CAM) and complementary and integrative medical procedures (CIM). Additionally, three latent variables were selected for the study and used in the confirmatory factor analysis (CFA) and structural equation model (SEM) LIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(47 reference statements)
0
5
0
Order By: Relevance
“… Shrestha (2021) has suggested that Cronbach’s Alpha α values should be ≥0.70. As such, this study is α values for the latent variables were 0.80–0.91, indicating acceptable internal consistency and scale reliability for the questionnaire items ( Daengneam et al, 2023 , p. 83).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“… Shrestha (2021) has suggested that Cronbach’s Alpha α values should be ≥0.70. As such, this study is α values for the latent variables were 0.80–0.91, indicating acceptable internal consistency and scale reliability for the questionnaire items ( Daengneam et al, 2023 , p. 83).…”
Section: Resultsmentioning
confidence: 65%
“… Bono et al (2019) also add that data distribution assessment usually includes a skewness and kurtosis test, with kurtosis typically done first ( Table 6 ). After examination, recommend acceptable values for kurtosis ≤ |7| and skewness ≤ |2| ( Daengneam et al, 2023 , p. 82). Thus, the skewness values of −0.30 to −1.24 are acceptable, as are the Kurtosis values of 0.03 to 2.50, indicating the CFA’s appropriateness.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 1: Six experts were assembled to review the results of the literature and document analysis and the subsequent development of a questionnaire for use by the educational institution's supervisors and administrators concerning their needs in executing their jobs. Content validity assessment was undertaken on each questionnaire item with the evaluation measured using the index of item-objective congruency (IOC) (Daengneam et al, 2023), with items having values of ≤ .50 deleted or revised (Taherdoost, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Other scholars have investigated SDLs' use in a team-based learning style of learner-determined needs and goals [ 66 , 67 ]. Using team-based learning, teachers can create flexible learning paths allowing learners to select their own learning components determined by their interests and needs.…”
Section: Literature Reviewmentioning
confidence: 99%